Complications in Endoscopic Ear Surgery. Issue 8 (September 2018) - Marchioni, Daniele; Rubini, Alessia; Gazzini, Luca; Alicandri-Ciufelli, Matteo; Molinari, Giulia; Reale, Marella; Presutti, Livio
Abstract : Objective: The aim of this study was to examine the premise that endoscopic ear surgery (EES) is associated with a low rate of complications (intraoperative and postoperative). Study Design: Retrospective review at two institutions. Setting: Tertiary referral center. Patients: The study included 825 patients who underwent exclusive EES between 2008 and 2016 at the Otorhinolaryngology-Head and Neck Surgery Department of Modena University Hospital, and between 2014 and 2016 at the Otorhinolaryngology-Head and Neck Surgery Department of Verona University Hospital. Interventions: Exclusive endoscopic ear surgery between 2008 and 2016 (tympanoplasties, second look or revision tympanoplasties, myringoplasties, stapedoplasties, canalplasties, ossiculoplasties, and exploratory tympanotomies). All surgical procedures were performed by two experienced surgeons. Main Outcome Measure: For each procedure, intraoperative, and early and delayed postoperative complications were evaluated. Results: The most common ear pathologies for which patients were sent for EES were cholesteatoma (33.6%), chronic otitis media (36.3%) and otosclerosis (26.8%). There was no case of major intraoperative complications such as injury to the dura or vascular structures. We observed minor intraoperative complications in 4.1% of the cases. Only 1.3% of patients experienced early postoperative complications. Delayed complications affected less than 1% of the cohort. Conclusions: Data from this study confirm the safety of the endoscopic technique, with very low complication rates, indicating that EES is a reliable therapeutic option, in particular, for tympanoplasties, myringoplasties, and stapedoplasties, as well as second look procedures. We have reported our experience with EES morbidity so that it can be compared with data from other centers using the same surgical technique.